HDL/ApoA-1 infusion and ApoA-1 gene therapy in atherosclerosis - Chyu, Kuang-Yuh; Shah, Prediman K. (Frontiers in Pharmacology, 2015)
The HDL hypothesis stating that simply raising HDL cholesterol (HDL-C) may produce cardiovascular benefits has been questioned recently based on several randomized clinical trials using CETP inhibitors or niacin to raise HDL-C levels. However, extensive pre-clinical data support the vascular protective effects of administration of exogenous ApoA-1 containing preβ-HDL like particles. Several small proof-of-concept clinical trials using such HDL/ApoA-1 infusion therapy have shown encouraging results but definitive proof of efficacy must await large scale clinical trials. In addition to HDL infusion therapy an alternative way to exploit beneficial cardiovascular effects of HDL/ApoA-1 is to use gene transfer. Preclinical studies have shown evidence of benefit using this approach; however clinical validation is yet lacking. This review summarizes our current knowledge of the aforementioned strategies.